Kebutuhan Model Pembelajaran Menulis Akademik Berbasis Higher Order Thinking Skills pada Mahasiswa Bahasa Arab - Renti Yasmar; Fitriyana Azizah (Al-Jawhar : Journal of Arabic Language, 2024)
Academic writing skills are core competencies that must be mastered by students in facing the demands of the academic world. However, in the context of Arabic Language Education, special challenges arise in developing quality writing skills. This article aims to identify the need for a Higher Order Thinking Skills (HOTS)-based learning model in teaching academic writing for students of the Arabic Language Education study program. A thorough literature review was conducted to explore an understanding of the HOTS concept and learning models that have been proven effective in improving academic writing skills. This article also discusses the challenges faced by Arabic Language Education students in developing academic writing skills, as well as providing strategic recommendations for integrating HOTS into the writing learning process. Thus, this article seeks to contribute to the understanding of the importance of using learning models that encourage higher-order thinking in the teaching of academic writing to Arabic Language Education students.